Histone Deacetylase 2 (HDAC2) Inhibitors Containing Boron. (16th June 2020) - Kavianpour, Poya; Gemmell, Madeleine C. M.; Kahlert, Jan U.; Rendina, Louis M.
Abstract: Histone deacetylase enzymes (HDACs) are responsible for the global silencing of tumour‐suppressor genes. Treatment with a histone deacetylase inhibitor (HDACi) can reverse this process and restore normal cell function. Herein, we report a small series of boron‐based (boronic acid, boronate ester and closo‐ 1, 2‐carborane) HDAC2 inhibitors with IC50 values in the nanomolar range. The boronate ester 4 b was the most potent compound assessed in this study (IC50 =40.6±1.5 nM), followed closely by the 1, 2‐ closo ‐carborane (IC50 =42.9±1.5 nM). Compound 4 b exceeds the potency of the related gold‐standard HDAC pan‐inhibitor vorinostat (1 ) toward this particular HDAC isoform. Abstract : Breaking the silence : We report the first boron‐based histone deacetylase inhibitors of HDAC2, which is known to silence tumour‐suppressor genes. With IC50 values in the nanomolar range, our compounds showcase boron's untapped potential in the design of new classes of epigenetic enzyme inhibitors.